Financial Literacy and Dynamic Environment on MSMEs Performance Throuhgh Digital Literacy in Batam - Hikmah; Mauli Siagian; Helmi Toatubun (Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to analyze Financial Literacy and Dynamic Environment through digital financial literacy on the Performance of Women MSMEs in Batam City. This study uses a quantitative research design using the covariance-based partial least square (PLS) testing method and the Sobel test for mediation testing. Data collection was conducted by distributing online questionnaires to female MSME actors spread across Batam City. This study used an associative research method. The data collection method used questionnaires. Using Jacob Cohen's formula, the sample in this study consisted of 204 respondents. The instrument used in this study was a questionnaire. The data were analyzed using SEM with the help of the Partial Least Square (PLS) program. The analysis results showed that financial literacy and dynamic environment had a positive and significant effect on MSME performance. In addition, digital financial literacy was proven to have a direct effect on MSME performance and mediated the effect of financial literacy and dynamic environment on performance. These findings emphasize the importance of digital financial literacy in improving the competitiveness and performance of MSMEs in the digital era.